Release of significant fraction of primary production as dissolved organic carbon in the Bay of Bengal. (February 2021) - Rao, D.N.; Chopra, M.; Rajula, G.R.; Durgadevi, D.S.L.; Sarma, V.V.S.S.
Abstract: Despite nutrients supply through river discharge, atmospheric deposition and eddy-driven mixing, low primary production in the Bay of Bengal (BoB) is attributed to light limitation and non-availability of nutrients during summer monsoon. We report here the first ever measurements of release of significant fraction of primary production as dissolved organic carbon (DOC) in the BoB through isotopic tracer experiments. Our results suggested that about half of the primary production is released as DOC due to existence of oligotrophic conditions, warm waters and dominance of picophytankton biomass during the summer monsoon. The mean Percentage of Extracellular Release (PER) ranged between 30 and 60% (mean of 45 ± 8%) suggesting that primary production through particulate organic matter measurements were significantly underestimated total primary production in the BoB. Higher DOC release compared to particulate organic carbon (POC) production was noticed in the cyclonic eddy (CE) regions, where high nutrients were found, than anticyclonic eddy (ACE) region, where balanced POC production and DOC release observed associating with warm waters and nutrient deplete conditions. This study suggests that primary production, including the DOC release, is not low than hitherto hypothesized due to lack of measurements on DOC and this study explains the paradox between low production and high sinking carbon fluxes to the deep BoB and underestimation of sequestration of atmospheric carbon dioxide through biological pump in the BoB. Highlights: Low nutrients concentrations were observed in the surface waters entire study region with low Chl-a. DOC release was close to that of POC production in the Bay of Bengal. Percentage Extracellular Rate is ~55% in the Bay due to dominance of picophytoplankton. Primary production in the Bay of Bengal is not lower than it is hypothesized.